Security of Information in Cloud Computing: A Systematic Review - Ansar, Mehreen; Shokat, Ijaz Ali; Fatima, Mubeen; Nazir, Kashif (American Scientific Research Journal for Engineering, Technology, and Sciences, 2018)
Data storage in cloud have become a great concern today. Many encryption and decryption methods have already been proposed to secure cloud data but everything comes with its pros and cons, this paper provides a critical overview of these cryptography techniques, issues and solutions regarding its security and availability.